Creativity in Context of Deviant Behavior - Kravtsov O.G (Moscow State University of Psychology and Education, 2019)
In this article author discussing the problem of creativity in context of studying of deviant behavior. The author shows the results of several research of criminal that are underage and normal teenagers creativity abilities. The results of this research appears to be paradoxical, pointing non-linear structure of creativity abilities. By the other words it could be not definitely assert, that low result by creativity tests means low creativity abilities of the respondents with deviant behavior. That is, adolescents with deviant behavior, doing poorly with creativity tests, show very high creative abilities, for example, in the social sphere. According author opinion one of the possible way of overcoming that difficulties is L.S. Vygotsky's cultural-historical approach. Studying of play activity and imagination development shows, that it is quality differences between deviant and normal persons. The author refers to them object level of development of imagination and stuck on the director's game, low level of imagination and lack of formation of the subject of imagination and play activity.